2009
DOI: 10.1242/dev.031369
|View full text |Cite
|
Sign up to set email alerts
|

Potential hepatic stem cells reside in EpCAM+ cells of normal and injured mouse liver

Abstract: Hepatic oval cells are considered to be facultative hepatic stem cells (HSCs) that differentiate into hepatocytes and cholangiocytes in severely injured liver. Hepatic oval cells have also been implicated in tumorigenesis. However, their nature and origin remain elusive. To isolate and characterize mouse oval cells, we searched for cell surface molecules expressed on oval cells and analyzed their nature at the single-cell level by flow cytometric analysis and in the in vitro colony formation assay. We demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
295
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 258 publications
(303 citation statements)
references
References 69 publications
8
295
0
Order By: Relevance
“…First, we examined the effect of FGF7 on LPCs in vitro. We found that a recombinant FGF7 stimulated the proliferation of HSCE1, a cell line derived from EpCAM + LPCs of adult mice (Okabe et al 2009), in a dose-dependent manner (Fig. 5A).…”
Section: Forced Expression Of Fgf7 Is Sufficient To Induce Expansion mentioning
confidence: 88%
See 2 more Smart Citations
“…First, we examined the effect of FGF7 on LPCs in vitro. We found that a recombinant FGF7 stimulated the proliferation of HSCE1, a cell line derived from EpCAM + LPCs of adult mice (Okabe et al 2009), in a dose-dependent manner (Fig. 5A).…”
Section: Forced Expression Of Fgf7 Is Sufficient To Induce Expansion mentioning
confidence: 88%
“…Among several major groups of paracrine factors, we especially focused on the FGF family because an LPC-specific marker, Trop2 (Okabe et al 2009), has previously been reported as a target gene of FGF10 in lung development (Lu et al 2005). We analyzed expression patterns of all of the paracrine Fgf ligands and found Fgf7 to be highly expressed, while we could not detect any expression of Fgf10 or Fgf3/22 belonging to the same subfamily (Supplemental Fig.…”
Section: Thy1mentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, cell populations that constitute the liver have been identified and defined mainly by their morphology and anatomic location. Rigorous efforts on identifying cell specific markers, especially surface antigens, such as EpCAM for biliary epithelial cells23 and stabilin‐2 for liver sinusoidal endothelial cells,28 have enabled prospective isolation and an in‐depth analysis of liver cell populations. Nevertheless, PFs have lacked a specific cell surface antigen for selective isolation.…”
Section: Discussionmentioning
confidence: 99%
“…A single‐cell suspension from the mouse liver was obtained by a two‐step collagenase perfusion method and used for preparing hepatocytes and nonparenchymal cells (NPCs) by centrifugal separation as described 23. Aliquots of cells were blocked with anti‐Fc receptor antibody, costained with fluorescence‐conjugated and/or biotin‐conjugated antibodies (listed in Supporting Table S1) and then incubated with allophycocyanin (APC)‐conjugated streptavidin (BD Biosciences) if necessary.…”
Section: Methodsmentioning
confidence: 99%